Efficiency Comparison of Micro-Nanobubble (Chan shrimp model I) with Air Disc and Airlift Aeration Systems in Intensive Indoor Red Tilapia Culture Ponds - Koydon, Supavadee; Is-haak, Jesada; Janhom, Indira; Ngamphongsai, Chansawang; Srisam, Vera; Tansakul, Vinij; Taparhudee, Wara (Burapha Science Journal, 2024)
Background and Objectives: Currently, the intensive farming of red tilapia is commonly practiced in indoor facilities, requiring an aeration system to provide dissolved oxygen levels suitable for the fish growth. Therefore, the objective of this study is to compare the efficiency of the micro-nanobubble aeration system, the Chan shrimp model I, with an air disc aeration system and an airlift aeration system under standard conditions and in intensive culture ponds of red tilapia in indoor facilities. Methodology: A randomized complete block design was applied with three treatments: T1) the air disc system, T2) the airlift aeration system, and T3) the micro-nanobubble aeration system with 99% oxygen concentration in the air. The block is designated as the experimental rounds or the day of experiment. The experiments were carried out in triplicate (3 days) and established using 3 round canvas tanks with a diameter of 3 m and filled with water to a depth of 70 cm to gain a total water volume of 4.95 m³. The efficiency of the three aeration systems was measured under two environments: standard condition using clean tap water, and culture water from the red tilapia canvas tank. Including the efficiency test in the Red tilapia culture ponds, where the fish with an average weight(+SD) of 244.92±0.21 - 245.46±0.15 g and an average length(+SD) of 21.16±0.42 - 21.27±0.23 cm were stocked at 500 fish/pond equivalent to 70.77 fish/m2 or 24.74±0.02 – 24.81±0.03 kg/m3. Temperature and dissolved oxygen changes were recorded and subsequently used to calculate the efficiency of the three aeration systems, as well as aeration system cost and energy cost. Main Results: Under standard environment of clean tap water, the standard oxygen transfer rate (SOTR; kgO2.hr-1) and standard aeration efficiency (SAE; kgO2.kW-1.hr-1) of the micro-nanobubble aeration system showed the highest efficiency with significant difference(p<0.05), followed by the airlift aeration system and the air disc system, respectively. Similarly, under the culture water environment, the micro-nanobubble aeration system had the significantly highest(p<0.05) standard oxygen transfer rate (SOTR, kgO2.hr-1) and standard aeration efficiency (SAE, kgO2.kW-1.hr-1). The airlift aeration system ranked second and followed by air disc aeration systems, respectively. The micro-nanobubble aeration system had the significantly lowest(p<0.05) total aeration cost percentage(+SD) (28.69±3.81%) compared to the airlift and air disc aeration systems, respectively. Additionally, the micro-nanobubble aeration system did deliver the highest cost saving(+SD) (71.31±3.81%) followed by the airlift aeration system and the air disc system, respectively. Furthermore, in the red tilapia pond, the micro-nanobubble aeration system demonstrated a significantly higher (p<0.05) field oxygen transfer rate (OTRf, kgO2.hr-1), aeration efficiency (AEf, kgO2.kW-1.hr-1), and power requirement (PR; W) than those of the airlift and air disc aeration systems, respectively. Conclusions: The micro-nanobubble aeration system, Chan shrimp model I, demonstrated the highest efficiency in increasing dissolved oxygen in water. Additionally, it reduced energy cost(+SD) as much as 57.09±1.41% and 14.22±2.40% compared to those of the air disc and airlift aeration systems, respectively.